2016
DOI: 10.1016/j.fuel.2016.07.095
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of simple global kinetic models for coal devolatilization with the CPD model

Abstract: Simulations of coal combustors and gasifiers generally cannot incorporate the complexities of advanced pyrolysis models, and hence there is interest in evaluating simpler models over ranges of temperature and heating rate that are applicable to the furnace of interest. In this paper, six different simple model forms are compared to predictions made by the Chemical Percolation Devolatilization (CPD) model. The model forms included three modified one-step models, a simple two-step model, and two new modified two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…However, since the thermal decomposition of solid fuel involves numerous reactions in parallel and in series over the process, multi‐step kinetic models have been proposed to evaluate the pyrolysis behaviour of coal and oil shale in literature, and so the other approach is carried out by a simplified multi‐step model assuming a number of paralleled n th ‐order reactions. The number of steps referring to the amount of kinetic pathways can be typically postulated to be two or three, while a larger number of steps has a risk of overfitting regardless of longer computation times . From this viewpoint, the degree of conversion and the rate equations for individual step and global ones can be expressed as: αi=Wi,0WiWi,0Wi,; α=iyiαi dαidt=Aiexptrue(EiRTtrue)true(1αitrue)ni; dαdt=iyidαidt yi=Wi,0Wi,W0W; iyi=1 where subscript i represents each individual step of the multi‐step model, and yi denotes the contribution of the i th step to the overall mass loss.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the thermal decomposition of solid fuel involves numerous reactions in parallel and in series over the process, multi‐step kinetic models have been proposed to evaluate the pyrolysis behaviour of coal and oil shale in literature, and so the other approach is carried out by a simplified multi‐step model assuming a number of paralleled n th ‐order reactions. The number of steps referring to the amount of kinetic pathways can be typically postulated to be two or three, while a larger number of steps has a risk of overfitting regardless of longer computation times . From this viewpoint, the degree of conversion and the rate equations for individual step and global ones can be expressed as: αi=Wi,0WiWi,0Wi,; α=iyiαi dαidt=Aiexptrue(EiRTtrue)true(1αitrue)ni; dαdt=iyidαidt yi=Wi,0Wi,W0W; iyi=1 where subscript i represents each individual step of the multi‐step model, and yi denotes the contribution of the i th step to the overall mass loss.…”
Section: Methodsmentioning
confidence: 99%
“…The number of steps referring to the amount of kinetic pathways can be typically postulated to be two or three, while a larger number of steps has a risk of overfitting regardless of longer computation times. [1,19,20] From this viewpoint, the degree of conversion and the rate equations for individual step and global ones can be expressed as:…”
Section: Non-isothermal Kineticsmentioning
confidence: 99%
“…They observed homogeneous ignition in both O 2 /N 2 and O 2 /H 2 O combustion environment but earlier ignition in the O 2 /H 2 O atmosphere than O 2 /N 2 at similar oxygen mole fraction due to the steam shift reaction in the O 2 /H 2 O atmosphere. Richards and Fletcher compared seven simple devolatilization models with well‐known CPD model and found that the modified two‐step model with distributed activation energy yielded close predictions with that of CPD while the simple single step model predictions were not comparable.…”
Section: Aspects Of Coal Combustionmentioning
confidence: 99%
“…They found homogeneous ignition for large particles and heterogeneous ignition for small coal particles. Cai et al 63 101 compared seven simple devolatilization models with well-known CPD model and found that the modified two-step model with distributed activation energy yielded close predictions with that of CPD while the simple single step model predictions were not comparable.…”
Section: Devolatilization Modelsmentioning
confidence: 99%
“…The second approach, on the other hand, consists of the use of global models and is easy to utilize due to its computational simplicity. These simple global kinetic models have been widely used in many studies (e.g., Andrew P. [19], Fei et al [20], and Piyarat et al [21]) to study the behavior of the pyrolysis process. Accordingly, the global pyrolysis kinetic models were adopted in this study.…”
Section: Non-isothermal Kineticsmentioning
confidence: 99%